Associations between Student–Teacher Relationship Quality, Class Climate, and Bullying Roles: A Bayesian Multilevel Multinomial Logit Analysis - Thornberg, Robert (Victims & offenders, 2022)
This study examined whether student–teacher relationship quality at the individual level and student–teacher relationship quality and peer climate at the class level were associated with being a bully, a victim, a bully/victim, or uninvolved in school bullying, controlling for gender, age, socioeconomic status and immigrant background at the individual level and socioeconomic status at the class level. Data from the Swedish Health Behavior in School-Aged Children (HBSC) survey from 2017/2018 were analyzed. In the current study, a sample of 3,578 students from 213 school classes was included. The findings showed that student–teacher relationship quality at the individual level was associated with a lower probability of being a bully, a bully/victim, or a victim compared to being uninvolved. In addition, class climate at the class level was associated with a lower probability of being a bully/victim or a victim compared to being uninvolved. Supportive class climate and student–teacher relationship is thus important dimensions to focus on in the everyday bullying prevention in school.